Nanoparticle-based photothermal heating to drive chemical reactions within a solid: using inhomogeneous polymer degradation to manipulate mechanical properties and segregate carbonaceous by-products. Issue 2 (13th December 2019) - Huang, Honglu; Firestone, Gabriel; Fontecha, Daniela; Gorga, Russell E.; Bochinski, Jason R.; Clarke, Laura I.
Abstract : Nanoparticle-based photothermal heating degrades polymer from the inside-out, creating pockets of depolymerized material around each nanoscale heating site. Abstract : Photothermal heating via metal nanoparticles is utilized to degrade polyethylcyanoacrylate (PECA), which undergoes a thermally-driven depolymerization process, resulting in (i) monomer loss from the sample, (ii) repolymerization to form shorter chains (oligomer), and (iii) formation of carbonaceous by-products which are graphene-like and luminescent. These unique PECA properties are used to demonstrate the heterogeneous temperature distribution present during photothermal processing and the results are compared to degradation via conventional methods where a uniform temperature is present. Photothermal heating results in formation of pockets of depolymerized material around each nanoscale heating site. The characteristic size of these photothermally-generated mechanical defects is determined from changes in the material's tensile strength. Changes in mass loss and molecular weight are utilized to determine the fraction of the sample that has depolymerized: distributing this volume equally to each heating site (based on the nanoparticle concentration) results in a volume that matches the defect size from independent mechanical measurements. In this way, macroscopic measurements elucidate the mesoscopic pattern of photothermal degradation. Sample morphology on scales from millimeters to nanometers is assessed via optical and electron microscopy. The carbonaceous by-products of degradation form in the hot region around each nanoparticle during photothermal heating, as revealed by transmission electron microscopy studies. Heterogeneous heating is also evident from optical images where starch granules, employed as an inert dilute additive to enhance PECA mechanical properties, also become luminescent due to degradation in "hot spots" created by the overlap of warm regions from nearby nanoparticle sites. Beyond the fundamental knowledge gained by these studies, the results demonstrate the ability to manipulate the connection between mechanical properties and chemical degradation which is important for developing new strategies for management of polymeric waste.